2001
DOI: 10.1038/sj.ejhg.5200696
|View full text |Cite
|
Sign up to set email alerts
|

Novel PKD1 deletions and missense variants in a cohort of Hellenic polycystic kidney disease families

Abstract: The autosomal dominant form of polycystic kidney disease is a very frequent genetically heterogeneous inherited condition affecting approximately 1 : 1000 individuals of the Caucasian population. The main symptom is the formation of fluid-filled cysts in the kidneys, which grow progressively in size and number with age, and leading to end-stage renal failure in approximately 50% of patients by age 60. About 85% of cases are caused by mutations in the PKD1 gene on chromosome 16p13.3, which encodes for polycysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Five participants, JHU602 (N=2), JHU100 (N=3), JHU588 (N=2), JHU411 (N=2) and JHU114 (N=2), had more than one PKD1 amino acid variant that met the criteria for pathogenicity (Supp Table 4). These observations raise the possibility that a combination of missense changes in cis might cooperatively result in a diminished level of functional protein [41].…”
Section: Class II Testsmentioning
confidence: 99%
“…Five participants, JHU602 (N=2), JHU100 (N=3), JHU588 (N=2), JHU411 (N=2) and JHU114 (N=2), had more than one PKD1 amino acid variant that met the criteria for pathogenicity (Supp Table 4). These observations raise the possibility that a combination of missense changes in cis might cooperatively result in a diminished level of functional protein [41].…”
Section: Class II Testsmentioning
confidence: 99%
“…They are shown in Supplemental Table 2, with the scores established to evaluate their putative pathogenicity by different programs (see Methods). Six were previously reported, 10,[12][13][14][15] and three were present in our in-house database: p.Thr2710N and p.Arg3183Gln were associated with another PKD1 or PKD2 mutation in patients diagnosed in the fourth decade, and the p.R3277C mutation was identified at the homozygous state in a woman transplanted at 50 years. No additional PKD1 or PKD2 variations were identified in the other patients.…”
mentioning
confidence: 99%
“…To exclude the possibility that the missense PKD2 variant on both of her alleles is a polymorphism, we screened 280 chromosomes from Greek healthy subjects originating from different areas of Greece and the mutated PKD2 allele was found in none of them. Reported molecular analyses on Greek PKD patients are limited [32,33]. All of the studies revealed mutations in the PKD1 gene [34]; another reported a de‐novo variant located in the REJ module in the long extracellular domain that was similar to our PKD1 variant.…”
Section: Discussionmentioning
confidence: 92%